Heparanase regulation of cancer, autophagy and inflammation: new mechanisms and targets for therapy. (16th November 2016) - Sanderson, Ralph D.; Elkin, Michael; Rapraeger, Alan C.; Ilan, Neta; Vlodavsky, Israel
Abstract : Because of its impact on multiple biological pathways, heparanase has emerged as a major regulator of cancer, inflammation and other disease processes. Heparanase accomplishes this by degrading heparan sulfate which regulates the abundance and location of heparin‐binding growth factors thereby influencing multiple signaling pathways that control gene expression, syndecan shedding and cell behavior. In addition, heparanase can act via nonenzymatic mechanisms that directly activate signaling at the cell surface. Clinical trials testing heparanase inhibitors as anticancer therapeutics are showing early signs of efficacy in patients further emphasizing the biological importance of this enzyme. This review focuses on recent developments in the field of heparanase regulation of cancer and inflammation, including the impact of heparanase on exosomes and autophagy, and novel mechanisms whereby heparanase regulates tumor metastasis, angiogenesis and chemoresistance. In addition, the ongoing development of heparanase inhibitors and their potential for treating cancer and inflammation are discussed. Abstract : By degrading heparan sulfate, heparanase impacts multiple signaling pathways that control gene expression, syndecan shedding and cell behavior. Heparanase also activates signaling at the cell surface via nonenzymatic mechanisms. This review focuses on recent developments that provide new insight into mechanisms of heparanase‐mediated regulation of cancer and inflammation, including its impact on exosomes, autophagy, angiogenesis, chemoresistance, cell migration and metastasis.